2018
DOI: 10.1017/s0021859618000813
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crop rotation and sheep grazing management on the seedbank and emerged weed flora under a no-tillage integrated crop-livestock system

Abstract: Effective integrated weed management in agricultural landscapes depends on the ability to identify and manage processes that drive weed dynamics. The current study reports the effects of grazing management and crop rotation strategies on the seedbank and emerged weed flora in an integrated crop-livestock system (ICLS) experiment during a 12-year period under no-tillage in sub-tropical southern Brazil. During winter, Italian ryegrass cover crops were grazed by sheep: grazing management treatments included two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Research on integration of livestock into cropping systems has produced a wide range of weed community responses (Tracy and Davis 2009, Hilimire 2011, McKenzie et al 2016, Schuster et al 2018, MacLaren et al 2019, Rosa‐Schleich et al 2019). These discrepancies stem from differences in duration of study, and location and system studied.…”
Section: Discussionmentioning
confidence: 99%
“…Research on integration of livestock into cropping systems has produced a wide range of weed community responses (Tracy and Davis 2009, Hilimire 2011, McKenzie et al 2016, Schuster et al 2018, MacLaren et al 2019, Rosa‐Schleich et al 2019). These discrepancies stem from differences in duration of study, and location and system studied.…”
Section: Discussionmentioning
confidence: 99%
“…No random effects of fields or farmers were observed for this relationship. Schuster et al (2018) showed the importance of straw in reducing weed emergence, which may explain why weed emergence decreased exponentially as the sward height increased (Fig. 2a).…”
Section: Weed Density and Diversity In An Iclsmentioning
confidence: 97%
“…Nevertheless, cover crops with high dry matter production and forage potential can also provide a source of grazing for livestock and thus provide an additional source of revenue for farmers and increase food production per unit area between successive grain crops (Moraes et al 2014;Nie et al 2016;Sulc and Franzluebbers 2014). However, many reports indicated that some of the benefits provided by cover crops depend on the amount of residue left on the surface (Webster et al 2016;Schuster et al 2018) and grazing of cover crops may have a direct impact on the residual straw amount (Hunt et al 2016). There is still a lack of information about the minimum sward height of winter grazed cover crops that does not negatively affect weed control benefits, as well as the sward height that promotes high meat production with the best combination of stoking rates and animal performance (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, a soybean-beef cattle rotation found that high grazing intensity (sward maintained to < 10 cm) increased the weed seed bank by more than threefold, whereas low grazing intensity (sward maintained to 30-40 cm) decreased the seed bank by 42% [102] . This was attributed to the taller sward outcompeting weeds.…”
Section: Initiatives To Re-integrate Crops and Livestock 41 New Rolementioning
confidence: 99%